Prognostic value of left atrial reverse remodelling in patients hospitalized with acute decompensated heart failure - Sakura Nagumo; Mio Ebato; Miki Tsujiuchi; Takuya Mizukami; Hideyuki Maezawa; Ayumi Omura; Megumi Kubota; Maho Ohmi; Yuki Numajiri; Hitomi Kitai; Tsutomu Toshida; Yoshitaka Iso; et al. (ESC Heart Failure)
Abstract Aims Left atrial (LA) volume index (LAVI) in chronic heart failure (HF) predicts cardiovascular outcomes. However, the association between LAVI reduction during acute decompensated HF (ADHF) and its prognostic potential is limited. We hypothesized that LA reverse remodelling (LARR) after ADHF therapy would be associated with better clinical outcomes. Methods This retrospective study analysed clinical outcomes and the LAVI reduction rate of 363 out of 861 patients hospitalized for ADHF who underwent two‐point echocardiography at admission and discharge between January 2015 and December 2019. The mean age was 74.3 ± 13.6 years, and the mean ejection fraction (EF) was 38.9 ± 15.2%. The follow‐up echocardiogram was performed 13.0 [9.5, 20] days after admission. As the median LAVI reduction rate was 7.02%, the LARR was defined as an LAVI reduction rate >7%. Results During the 34.0 ± 20.2 months of follow‐up, 117 patients (32.2%) reached the primary endpoint defined as cardiovascular death and rehospitalization for ADHF. Kaplan–Meier survival analysis showed that patients with LARR had a better prognosis. Multivariate analysis indicated that LARR was an independent predictor of cardiovascular events. Similar findings were observed in the subgroup analyses of patients with persistent/permanent atrial fibrillation and those with non‐HF with reduced EF. Among patients who were brain natriuretic peptide (BNP) responders, defined as a relative reduction of >70% in BNP from admission to discharge, non‐LARR was observed in 41.6%. BNP responders without LARR experienced worse prognoses. Conclusions LARR in the early vulnerable phase after hospitalization for ADHF was associated with better long‐term clinical outcomes.